PENETAPAN ASAL USUL ANAK DARI PERKAWINAN POLIANDRI LIAR KEPADA AYAH BIOLOGISNYA (STUDI ANALISIS TERHADAP PUTUSAN PENGADILAN AGAMA BUKIT TINGGI NOMOR 321/PDT.G/2022/PA. BKT) - Jumni Nelli; Srifinora (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
This study aims to find out what is the legal consideration of the Panel of Judges in the case of validating the origins of children from illegal polyandry marriages, in which it is decided that the child is assigned to his biological father. This study uses a type of normative legal research which is analyzed qualitatively with the case approach research method, conceptual approach and comparative approach. The sources and types of materials in this study are primary legal materials, namely the judge's determination No. 321/Pdt.G/2022/PA. Bkt. Secondary legal materials include legal science books, legal journals, legal reports and print and electronic media. The results of the research show that the judge granted the request for legalization of the origin of children from wild polyandry marriages assigned to their biological father based on their considerations on legal facts at trial and the views of the clergy as a symbol of living values ​​in society as stated in Article 5 paragraph (1) of the Law Number 48 of 2009 concerning Judicial Power, in addition to that the judges have also carried out studies of various viewpoints from philosophical, juridical to sociological, very appropriate in the context of achieving maqâshid al-syarî'ah in terms of offspring maintenance (hifzh al-nasl) and concerning children's rights and protection of children besides that according to social law children are also entitled to get guardianship rights, affection, maintenance and inheritance rights from their father.